An Efficient Response to ISIS in Cyberspace: Public-Private Partnership - (:unkn) unknown (IOS PRESS, 2017)
The main aim of terrorists is to spread fear and panic in society. This has been facilitated by widespread use of the Internet and communications technologies. Social media is considered to be one of the most prominent platforms that can be used to effectively shape public opinion in order to reach desired outcomes. Terrorist organisations have always been aware of this fact, and have utilised cyberspace not only for propaganda and the promotion of their own narratives, but for a wide range of purposes, including recruitment, secret communication, and financial transactions. From the initial terror attacks that put ISIS in the spotlight, the terrorist organisation has efficiently been making use of the unique features of this technology, both actively and passively. In addition to the uses listed above, ISIS supporters have conducted cyber-attacks on crucial targets, differentiating themselves from other violent extremists, and pushing those countries fighting against ISIS to generate a specific cyber-strategy which has become an integral part of the war on terror. This chapter sets out to examine the cyberspace activities of ISIS, with a particular focus on the Paris attacks of 2015 and the subsequent Western responses. The aim is twofold: firstly, to provide an insight into terrorist use of cyberspace, with specific examples of the ways that ISIS militants and supporters exploit a wide array of methods and tools with the aim of sustaining legitimacy and operational security; secondly, this paper analyses Western responses to ISIS activities in cyberspace with an emphasis on the role of technology companies in disrupting and destructing the terrorist organisation's cyber-operations. The discussion concludes with a consideration of the partnership possibilities between nation-states and technology companies, which, in the aftermath of the Snowden leaks, come at a time when trust between the two entities has been deeply shaken.
Keywords: ISIS; cyber-terrorism; NATO; Public-Private Partnership